Program Lembaga Model Desa Konservasi (LMDK): Evaluasi dan Implikasinya terhadap Kesejahteraan Masyarakat - Khusnul Khotima; Noval Maliki (Empower : Jurnal Pengembangan Masyarakat Islam, 2023)
The Conservation Village Model Institute (LMDK) is one of the Ministry of Forestry's policies aimed at buffer village communities or communities living around conservation areas. LMDK appeared when the function of the Mount Ciremai area was converted into a National Park area on October 19, 2004. One of the buffer villages that received the LMDK program was Linggasana Village, Cilimus District, Kuningan Regency. The purpose of this research is to describe the implementation of the Linggasana Village LMDK program and its implications for community welfare which can be represented by the standard of living of the people. The method used in this research is descriptive-qualitative. Informant withdrawal techniques using purposive and using three data collection techniques, namely observation, interviews, and documentation. After the data is collected, the next step is triangulation or merging. The results of this study indicate that the existing LMDK program in Linggasana Village is no longer running. This is due to several factors, both from the community and from the government itself. But basically, the non-performance of the LMDK program was the government's mistake in designing an empowerment program for the buffer village community, so that the existing LMDK program in Linggasana Village was unable to answer the needs of the Linggasana community itself.